Upholding the right to health of forcibly displaced children in Europe - Amy Stevens; Zeliha Öcek; Sergey Sargsyan; Michelle Black (Public Health in Practice, 2025)
In 2023 Europe hosted an estimated 9 million children who had been forcibly displaced from their homes because of conflict, persecution, violence, natural or environmental disasters, climate crisis, human trafficking and extreme poverty. Their experiences pre, during and post migration impact their health, wellbeing and development. Countries across the European Region have a moral and legal duty to uphold the right to health of all children living within their borders, irrespective of immigration status. However, many countries are falling short of delivering on these obligations. The rise in populist radical right politics and anti-immigrant sentiment across the Region has led to an increase in potentially health-harming immigration policies and practices. Challenges to meeting the health needs of displaced children include underfunded health systems, limited specialist services, health and care workforce shortages, and lack of data to inform evidence-based policy and practice. Displaced children are often subjected to restrictions on service entitlements; systemic racism, xenophobia and discrimination in health systems; and language, cultural, social, financial, and administrative barriers to care. Cross-country collaboration is required to address the drivers of forced migration; increase availability of safe and legal routes for refugees; and ensure health systems across the Region have the data, resource and capacity required to respond to the needs of displaced children. Essential policies supporting a child's right to health include: provision of child and family-centred community alternatives to refugee camps and immigration detention; provision of healthcare and education entitlements equitable to children of the host nation; protection of children from violence and exploitation; and delivery of quality and inclusive trauma-informed healthcare that accounts for language needs, cultural diversity and safeguarding risks. With political commitment and coordinated efforts, ensuring the right to health for displaced children is achievable and should be prioritised.